The Role of circTmeff-1 in Morphine Addiction Memory of Mice - Hailei Yu; Boyang Wen; Yun Lu; Bing Xie; Feng Yu; Minglong Zhang; Chunling Ma; Bin Cong; Di Wen; Haitao Bi (Cells, 2023)
In addition to the essential pharmacological effects of opioids, situational cues associated with drug addiction memory are key triggers for drug seeking. CircRNAs, an emerging hotspot regulator in crown genetics, play an important role in central nervous system-related diseases. However, the internal mediating mechanism of circRNAs in the field of drug reward and addiction memory remains unknown. Here, we trained mice on a conditional place preference (CPP) model and collected nucleus accumbens (NAc) tissues from day 1 (T0) and day 8 (T1) for high-throughput RNA sequencing. QRT-PCR analysis revealed that circTmeff-1 was highly expressed in the NAc core but not in the NAc shell, suggesting that it plays a role in addiction memory formation. Meanwhile, the down-regulation of circTmeff-1 by adeno-associated viruses in the NAc core or shell could inhibit the morphine CPP scores. Subsequently, the GO and KEGG analyses indicated that circTmeff-1 might regulate the addiction memory via the MAPK and AMPK pathways. These findings suggest that circTmeff-1 in NAc plays a crucial role in morphine-dependent memory formation.